Optimalisasi Supervisi Akademik dapat Meningkatkan Kinerja Guru Dalam Perencanaan Pelaksanaan Pembelajaran di SMPN 6 Muntok Semester Ganjil Tahun Pelajaran 2020/2021 - Masrul Masrul (Jurnal Ilmiah Wahana Pendidikan, 2023)
The low quality of the learning process at SMPN 6 Muntok, Muntok District, West Bangka Regency is caused by teachers in carrying out the learning process. This research method is action research which is carried out in two cycles. The results of the study improved teacher performance in the preparation of the rpp as a whole was in the pre-cycle by 75% after the first cycle action to 82%, and after the second cycle action increased again to 96%. For the implementation of learning, the overall improvement of teacher performance was in the Pre-cycle by 77% after the first cycle action to 84%, and after the second cycle action increased again to 91% (very good category). Based on the results of the above action research can be concluded as follows. Academic supervision through individual guidance carried out by the principal on teachers can improve teacher performance at SMP Negeri 6 Mentok Kecamatan Muntok Kabupaten Bangka Barat for the 2018/2019 Academic Year in learning management, both aspects of learning planning and learning implementation. This is shown from the results of observations on RPP from pre-cycle to cycle I there was an increase in the average score of 7%, from pre-cycle to cycle II 21%, from cycle I to cycle II 14%. Similarly, the average score of the learning implementation process from pre-cycle to cycle I was 7%, from pre-cycle to cycle II 14%, from schyklus I to cycle II 7%.